Dual role of circulating and mucosal Vδ1 T cells in the control of and contribution to persistent HIV-1 infection - Brendan T. Mann; Marta Sanz; Matthew L. Clohosey; Kayley Langlands; Alisha Chitrakar; Carles Moreno-Soriano; Joana Vitalle; Marie Anne Iannone; Ezequiel Ruiz-Mateos; Claire Deleage; Marc Siegel; Natalia Soriano-Sarabia (Nature Communications)
Abstract Curative strategies for human immunodeficiency virus (HIV-1) infection are hindered by incomplete characterization of the latent reservoir and limited enhancement of anti-HIV immune responses. In this study, we identify a dual role for peripheral and tissue-resident Vδ1 T cells within the gastrointestinal mucosa of virally suppressed people with HIV. Phenotypic analyses identify an increased frequency of highly differentiated, cytotoxic effector Vδ1 T cells that inhibit HIV-1 replication in vitro coinciding with increased degranulation and IFN-γ production. Conversely, we detect an enrichment of HIV-1 DNA in tissue-resident CD4 + Vδ1 T cells in situ. Despite low CD4 expression, we find circulating Vδ1 T cells also contain HIV-1 DNA which is replication-competent. We show that T cell receptor-mediated activation of peripheral Vδ1 T cells induces de novo upregulation of CD4 providing a plausible mechanism for increased permissibility to infection. These findings highlight juxtaposing roles for Vδ1 T cells in HIV-1 persistence including contribution to tissue reservoirs.